Factors contributing to failure likelihood of Strategic Alliances - Lee, Cheon Loon (2008)
This study examines the factors contributing to the failure likelihood of strategic alliances, focusing on the age of alliances, and the age and size of alliance participants. With past research on the honeymoon effect, social exchange theory, and structural inertia, we hypothesize a relationship between these factors and failure likelihood.